Nursing organizational climates in public and private hospitals - García, I García (Nursing ethics, 2014)
Background:Researchers study climate to gain an understanding of the psychological environment of organizations, especially in healthcare institutions. Climate is considered to be the set of recurring patterns of individual and group behaviour in an organization. There is evidence confirming a relationship between ethical climate within organizations and job satisfaction.Objectives:The aim of this study is to describe organizational climate for nursing personnel in public and private hospitals and to confirm the relationships among the climate variables of such hospitals.Materials and methods:A correlational study was carried out to measure the organizational climate of one public hospital and two private hospitals in Granada. The Work Environment Scale was used for data collection. The Work Environment Scale includes 10 scales, ranging from 0 to 9, which were used to evaluate social, demographic and organizational climate variables. In this study, 386 subjects were surveyed in three hospitals.Results: A total of 87% of the participants were female and 16% were male. Most participants were nurses (65.6%), followed by nursing aides (20%), and technicians (14.4%). The results obtained reflected different patterns of organizational climate formation, based on hospital type (i.e. public or private) within the Spanish context. Most of the dimensions were below the midpoint of the scale.Discussion and conclusions:In conclusion, in public hospitals, there is a greater specialization and the organizational climate is more salient than in the private hospitals. In addition, in the public hospitals, the characteristics of the human resources and their management can have a significant impact on the perception of the climate, which gives greater importance to the organizational climate as decisive of the ethical climate.